First Molecular Identification and Whole Genome Sequencing of Listeria monocytogenes Isolated From an African Lion - Ping Xu; Xinyong Qi; Xiaoxu Wang; Feng Xu; Hongjin Zhao; Liping Shen; Yujie Zhang; Shixin Huang; Jian Wang (Veterinary Medicine and Science)
ABSTRACT Listeria monocytogenes (LM) is a zoonotic pathogen that causes sporadic infectious listeriosis, which is a foodborne disease associated with consumption of contaminated food or feed. The internal organs of an African lion from a zoo in Shanghai were analysed to determine the cause of death. LM infection was suspected on the basis of the clinical symptoms and pathological changes and confirmed by polymerase chain reaction, whole genome sequencing and phylogenetic analysis. This is the first report of LM infection of an African lion in China.